Static analysis of sophisticated cable arrangement on pedestrian bridge - Dzul Helmi, Arifin (2014)
The purpose of this research is to study the principal theory of Cable stayed bridge and analyse the behaviour of cable stayed with sophisticated arrangement of cable stays. In this study, static analysis of pedestrian bridge had investigated. Static analysis is to determine the maximum and minimum stress on cable and deck, checking the maximum deflection, resultant moment and strain on the pedestrian bridge at sophisticated cable arrangement to compares with the conventional arrangement. In addition, sensitivity analysis is done to determine the behaviour of the cables when some parameters had changed to determine the analysis of the bridge when some parameters changed (high of pylons) due to static analysis. The important of this study came out when engineers hard to make a choice to build a bridge from design to the actual structure while maintaining aesthetic values. Aesthetic values are very important to maintain the identity of a bridge and thus become a landmark for the country. The design loads which are pedestrian loads are distributed to the joints on bridge deck. A total of each case will analyse three arrangement cables which are conventional arrangement (harp and fan) and a sophisticated arrangement, this study had been analyse using LUSAS software. The result shown, that the fan arrangement is ideal and suitable in construction for short-, span structure while harp pattern is not the best from the static or economic point of view; it is attractive because of its undeniable aesthetic advantages. Thus, sophisticated arrangement is also very ideal arrangement because the static analysis results between the conventional arrangements. Furthermore it can maintain the aesthetic value.